2021
DOI: 10.1002/jcsm.12705
|View full text |Cite
|
Sign up to set email alerts
|

Association of sarcopenia with mortality and end‐stage renal disease in those with chronic kidney disease: a UK Biobank study

Abstract: Background Sarcopenia, a degenerative and generalized skeletal muscle disorder involving the loss of muscle function and mass, is an under‐recognized problem in clinical practice, particularly in chronic kidney disease (CKD). We aimed to investigate the prevalence of sarcopenia in individuals with CKD, its risk factors, and its association with all‐cause mortality and progression to end‐stage renal disease (ESRD). Methods UK Biobank participants were grouped according to the presence of CKD (defined as an esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
86
1
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 115 publications
(95 citation statements)
references
References 64 publications
5
86
1
3
Order By: Relevance
“…Understanding the causal mechanisms that underpin uraemic cachexia is key for the development of therapeutic interventions to combat this debilitating co‐morbidity in people with kidney disease. Research conducted within this patient population has shown that uraemic cachexia manifests early in the disease process 29 and as such, targeting patients in stages G1–4 may allow for a preventative approach to management. 30 Progress in understanding such uraemic skeletal muscle cachexia has predominantly been conducted in patient populations, 2 , 3 , 6 , 7 , 31 with any cellular work to this point using immortalised cells lines.…”
Section: Discussionmentioning
confidence: 99%
“…Understanding the causal mechanisms that underpin uraemic cachexia is key for the development of therapeutic interventions to combat this debilitating co‐morbidity in people with kidney disease. Research conducted within this patient population has shown that uraemic cachexia manifests early in the disease process 29 and as such, targeting patients in stages G1–4 may allow for a preventative approach to management. 30 Progress in understanding such uraemic skeletal muscle cachexia has predominantly been conducted in patient populations, 2 , 3 , 6 , 7 , 31 with any cellular work to this point using immortalised cells lines.…”
Section: Discussionmentioning
confidence: 99%
“…In a retrospective study of 225 Italian adults of both genders diagnosed with NAFLD, sarcopenia prevalence increases progressively with the severity of liver fibrosis. It rises from 22.2% in the absence of fibrosis to 60.0% in patients with stage 4 fibrosis [24] .…”
Section: Correlation Of Sarcopenia and Nafldmentioning
confidence: 92%
“…Sarcopenia is predominantly a geriatric condition, but young and middle-aged people are at risk of developing it due to multiple factors that are not primarily related to aging per se. Malnutrition, diabetes, hormonal imbalances, low physical activity, or comorbidities such as cancer [21] , chronic respiratory diseases [22] , mental diseases [23] , hepatic diseases [24] , renal failure [25] , Cushing's syndrome [26] , genetic predisposition, and the effects of environment in early development are all associated with the development of muscle wasting [27,28] .…”
Section: Etiologymentioning
confidence: 99%
“…Markers of muscle mass, strength, and functional capacity are important predictors of outcomes in this patient population subjected to a catabolic protein-energy wasting (PEW) syndrome and consequently, muscle atrophy ( Chatzipetrou et al, 2022 ; Sabatino et al, 2021 ). Importantly, assessment of muscle functionality may provide additional diagnostic and prognostic information to clinical outcomes, quality of life, and mortality rates ( Wilkinson et al, 2021 ).…”
Section: Effects Of Bfr Exercise On Physical Fitness Physical Functio...mentioning
confidence: 99%